O loteamento fechado e o rateio das despesas comuns - Valesi, Raquel Helena (2006)
People s need for a better quality of life has led them to create new ways the land. One of those ways is found in the so-called gated developments, a social phenomenon generated by the insecurity that afflicts cities. Although these common interest developments are based on the principles of horizontal property, there is no specific legislation governing them. Thus, because an atypical condominium is born within these developments, owners form homeowners associations for the delivery of basic services (trash collection, gate control, water abstraction and distribution, sanitation, road maintenance, surveillance, among others) to that social group. In the face of such a unique situation inside gated developments, which require the delivery of such services, since they are not provided by the city government, a number of owners and committed purchasers, even though they directly or indirectly enjoy the benefit of such services, refuse to participate in the monthly expenses of those services with the excuse that they are not members of the homeowners association, finding support in subparagraph XX of article 5th of the Brazilian Constitution. In this essay, besides trying to define what actually is a gated development, we will also seek to demonstrate how a legal bond between a homeowners association and a property owner is formed. Although legally not confounded with the configuration of the condominium under Law 4.519/64, a gated development or the association formed by the owners of individual lots is, in fact, similar since both require the delivery of communal services that benefit all constituents of this collectivity, affording them enhanced conveniences and security and appreciating their properties, so that non-participation in the common expenses would imply actual unjustified enrichment, which is illicit under Brazilian law